Return On Assets Sebagai Pengukuran Perputaran Modal Kerja dan Piutang PT AKR Corporindo Tbk - Lisdawati; Faisal Ardiansyah (Coopetition : Jurnal Ilmiah Manajemen, 2021)
Financial performance can be a future or prospect whose development potential is very good for company growth. Working capital is a separate and fundamental problem that company managers often face in managing equity and assets. In contrast, Receivables, which are part of the working capital component, have a turnaround or cycle related to the sale of commodities, cash flow, and cash receipts. The turnover describes good financial condition. The study population used financial statement data at PT AKR Corporindo Tbk in 2005-2019. The purpose of this research is to specifically examine and prove the measurement of Working Capital and Accounts Receivable Turnover and its impact on Return On Assets empirically. Data analysis used multiple regression analysis with Statistic / Data Analysis software STATA MP14 Version. This study indicates that the turnover of working capital and accounts receivable turnover does not increase Return on Assets either partially or simultaneously. The Return On Assets contribution is influenced by 16.88 percent of the Working Capital Turnover, Accounts Receivable Turnover, and Company Size factors as control variables.